Characteristics Of Purple Waxy Corn Yoghurt Powder (Zea mays var ceratina kulesh) With The Foam Mat Drying Method (Study Of The Addition Of Maltodextrin And Tween 80) - Wairooy, Rachmalia Atika Salma; Rosida (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
This study's main ingredient in making yogurt powder is purple waxy corn. This study studied the making of purple waxy corn yoghurt powder because it contains a lot of anthocyanins and antioxidants. To speed up the delivery process and maintain the viability of lactic acid bacteria and other heat-resistant compounds, it is necessary to add maltodextrin and tween 80. This study aimed to analyze the effect of the addition of maltodextrin and tween 80 on the characteristics of yogurt powder and determine the best treatment combination of these variations. The method used was a Complete Random Design (RAL) with a 3x3 setup, where Factor I was the amount of maltodextrin added (6%, 10%, 14%) and Factor II was the amount of tween 80 added (0.8%, 1%, 1.2%). We analyzed the obtained data using ANOVA, followed by a further DMRT test of 5%. The results showed a real interaction (p?0.05). Purple waxy corn yogurt powder with the addition of maltodextrin 14% and tween 80 1.2% is the best treatment that produces yogurt powder with a moisture content value of 3.66; ash content 0.5; solubility 88.03; viscosity 283; total dissolved solids 17.75; pH 4.56 total BAL 8.45 log. CFU/ml; antioxidant activity 65.25 and protein 0.39. The organoleptic characteristics yielded scores of 4.32 for color, 4.20 for texture, 4.04 for aroma, and 4.28 for taste. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-BeingSDG 9: Industry, Innovation, and InfrastructureSDG 12:: Responsible Consumption and Production